Political philosophies of Plato and Hegel - Foster, M. B. (London, 1968)
This is a critical study of the political doctrines contained in two works, Plato's Republic and Hegel's Philosophy of Right and endeavours to throw light on each by relation to the other. Not technical in method, its aim is to contribute to the understanding of what is familiar and essential in these two works of fundamental importance to all students of political philosophy.
Keywords: Political Science